Electrocardiographic findings in patients with symptoms of infection by Dengue, Chikungunya and Zika virus Centro Cardiovascular Regional ASCARDIO (Boletin Médico de Postgrado, 2022)
Tropical Cardiology comprises a group of diseases with serious consequences in the cardiovascular system. The infection by the DENV (dengue), Chikungunya and ZICV (Zika) virus are responsible for various disease that despite being transmitted by the same vector, have different symptomatology and alterations in the myocyte. The aim of this study was to describe the electrocardiographic findings in patients with symptoms suggestive of infection by the previously mentioned virus that attended the Regional Cardiovascular Center ASCARDIO during the period September-November 2018.  A descriptive, cross-sectional design, was carried out that included 20 patients with viral symptoms from which a 12-lead electrocardiogram was obtained. 60% of patients had symptoms suggestive of infection by DENV, 25% by Chikungunya virus and 15% by ZICV. All patients had some type pf electrocardiographic abnormality. The most predominant alteration was the presence of supra-level ST segment (50%) followed by rhythm disorders (40%) and conduction disorders (10%). Electrocardiographic abnormalities are common in patients with symptoms suggestive of infection by these tropical viruses which warrants the need of cardiologic evaluation in this group of patients.
Keywords: virus; dengue; zika; chikungunya; electrocardiography